Histologic surveillance after liver transplantation due to autoimmune hepatitis. Issue 5 (12th April 2017) - Puustinen, Lauri; Boyd, Sonja; Arkkila, Perttu; Isoniemi, Helena; Arola, Johanna; Färkkilä, Martti
Abstract: Background: Autoimmune hepatitis (AIH) often recurs after liver transplantation (LT). Our aim was to evaluate the recurrence rate of AIH after LT, impact of AIH recurrence on survival and fibrosis progression, and find risk factors for AIH recurrence. Methods: Forty‐two patients with AIH prior to LT with ≥1 protocol biopsy ≥1 year post‐LT were included with a median follow‐up of 5.0 years (1.0‐17.0). Follow‐up liver biopsies were re‐evaluated for AIH recurrence, fibrosis progression, and cirrhosis development. Results: A histological recurrence of AIH was diagnosed in 15 (36%) patients at a median of 5 years of follow‐up. Recurrent AIH lead to progressive fibrosis (METAVIR stage 3‐4) in two but did not cause a single patient or graft loss. Transaminases were normal in three patients with recurrent AIH (20%). AIH recurrence was more common in patients with no overlapping cholangitis (OR 1.44, P =.021). Immunosuppression without antimetabolite increased the risk of AIH recurrence (OR 1.47, P =.018). Patient and graft survival rates at 1, 5, and 10 years were 94%, 86%, and 86% and 91%, 77%, and 74%. AIH recurrence did not affect survival. Conclusions: AIH recurrence occurs in 36% in 5 years, but does not affect patient or graft outcome.